Proceedings of the 2017 Conference on Empirical Methods in Natural Language Processing 2017
DOI: 10.18653/v1/d17-1195
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Entity Representations in Neural Language Models

Abstract: Understanding a long document requires tracking how entities are introduced and evolve over time. We present a new type of language model, ENTITYNLM, that can explicitly model entities, dynamically update their representations, and contextually generate their mentions. Our model is generative and flexible; it can model an arbitrary number of entities in context while generating each entity mention at an arbitrary length. In addition, it can be used for several different tasks such as language modeling, corefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 27 publications
0
108
0
Order By: Relevance
“…State-of-the-art approaches on these tasks are inherently entity-centric. Separately, it has been shown that entity-centric language modeling in a continuous framework can lead to better performance for LM related tasks Ji et al, 2017). Moreover, external data has shown to be useful for modeling process understanding tasks in prior work , suggesting that pre-trained models may be effective.…”
Section: Background: Process Understandingmentioning
confidence: 99%
“…State-of-the-art approaches on these tasks are inherently entity-centric. Separately, it has been shown that entity-centric language modeling in a continuous framework can lead to better performance for LM related tasks Ji et al, 2017). Moreover, external data has shown to be useful for modeling process understanding tasks in prior work , suggesting that pre-trained models may be effective.…”
Section: Background: Process Understandingmentioning
confidence: 99%
“…Perplexity We evaluate our model using the standard perplexity metric: exp 1 T T t=1 log p(x t ) . However, perplexity suffers from the issue that it PPL UPP ENTITYNLM * (Ji et al, 2017) 85.4 189.2 EntityCopyNet * 76.1 144.0 AWD-LSTM (Merity et al, 2018) overestimates the probability of out-of-vocabulary tokens when they are mapped to a single UNK token. This is problematic for comparing the performance of the KGLM to traditional language models on Linked WikiText-2 since there are a large number of rare entities whose alias tokens are outof-vocabulary.…”
Section: Resultsmentioning
confidence: 99%
“…• AWD-LSTM (Merity et al, 2018): strong LSTM-based model used as the foundation of most state-of-the-art models on WikiText-2. • ENTITYNLM (Ji et al, 2017): an LSTM-based language model with the ability to track entity mentions. Embeddings for entities are created dynamically, and are not informed by any external sources of information.…”
Section: Evaluation Setupmentioning
confidence: 99%
“…Recently, entity tracking has been popular for generating coherent text (Kiddon et al, 2016;Ji et al, 2017;Clark et al, 2018). Kiddon et al (2016) proposed a neural checklist model that updates predefined item states.…”
Section: Memory Modulesmentioning
confidence: 99%
“…Kiddon et al (2016) proposed a neural checklist model that updates predefined item states. Ji et al (2017) proposed an entity representation for the language model. Updating entity tracking states when the entity is introduced, their method selects the salient entity state.…”
Section: Memory Modulesmentioning
confidence: 99%